IGBT Energy Dissipation Model Based on Matlab and Its Application in Thermal Simulation - CHEN Yan; XU Peng; LI Shiping (Kongzhi Yu Xinxi Jishu)
It introduced a new method of IGBT thermal simulation based on Matlab. With this new method,thermal simulative model of TIM1500ESM33-TS type IGBT was built by Simulink and S-Function. It has been applied in the simulation of three-phase two-level SVPWM inverter. The simulation results show that this method can get accurate real-time power loss and real-time junction temperature of IGBT. Furthermore, this method has applied the real-time current as input variable, so it can be used to simulate IGBT under different work conditions.